Dominance of large trees in carbon storage of Peruvian Amazon forest - Lozano, Andi (2026)
Introduction: Forest carbon accumulation is crucial to mitigate ongoing climate change, as large individual trees store a substantial portion of the total carbon in biomass. In this study, large trees and carbon storage were estimated in five forests in the Peruvian Amazon. Methods: For the study, 100 plots were selected (twenty 500 m2 plots per forest site), distributed between 382 to 2086 meters above sea level. Various relationships were explored between the diameter at breast height (DBH) of the most abundant tree species and above- and below-ground carbon. The average carbon content in the tree was calculated based on 50% of the total tree volume at five sites of the Peruvian Amazon. Results: The site with most tree species (Alto Mayo Forest), had 59 tree species. The species Brosimum alicastrum, Ficus insipida, Manilkara bidentata, Inga sp., and Pourouma cecropiifolia showed an average aboveground carbon of 2.31, 3.09, 2.52, 2.78, 2.93 t ha-1, respectively, and values of 0.35, 0.48, 0.38, 0.42 and 0.43 t ha-1 of belowground carbon in trees with ≥ 46 cm DBH. Nectandra sp. showed an above and belowground carbon of 2.50 and 0.38 t ha-1 in trees with ≥ 46 cm DBH, while Cedrelinga catenaeformis showed averages of 5.21 and 0.74 t ha-1 of above and belowground carbon in trees with ≥ 61 cm DBH. Discussion: It was concluded that given the urgency of keeping carbon reserves out of the atmosphere, it is necessary to conserve trees larger than 41 cm, this also allows conserving forest biodiversity and microfauna by buffering the microclimate in the face of future climate changes.